2017
DOI: 10.1093/jac/dkw556
|View full text |Cite
|
Sign up to set email alerts
|

Extended stability of antimicrobial agents in administration devices

Abstract: This review found no published studies that comply with UK national standards for stability testing. We recommend further research and publication of antimicrobial stability data to support OPAT within the antimicrobial stewardship agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Using methods that are consistent with recent recommendations,2 elastomeric infusion devices for ambulatory care containing a total daily dose of ceftolozane–tazobactam in 240 mL remain stable for 24 hours at 21°C and 37°C. There were no appreciable concentration-related effects on drug stability.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Using methods that are consistent with recent recommendations,2 elastomeric infusion devices for ambulatory care containing a total daily dose of ceftolozane–tazobactam in 240 mL remain stable for 24 hours at 21°C and 37°C. There were no appreciable concentration-related effects on drug stability.…”
Section: Discussionmentioning
confidence: 83%
“…Published in vitro stability data for ceftolozane–tazobactam supports intermittent short duration infusions at a standard dose of 1.5 g three times a day 1. Thrice daily visits are not practical for many outpatient parenteral antimicrobial therapy (OPAT) services and measures to facilitate once daily visits, such as continuous 24-hours infusions are preferred 2. A recent case report demonstrated the clinical utility and likely stability of ceftolozane–tazobactam administered as a continuous infusion by elastomeric infusion device 3.…”
Section: Introductionmentioning
confidence: 99%
“…Unreliable data regarding stability of such antibiotics may have serious consequences since clinicians may use these results to promote continuous infusion over a prolonged period. This issue raises the need for clinicians to seek pharmaceutical expertise in order to assess the level of proof of the analytical methods used to provide data having clinical impact [33].…”
Section: Discussionmentioning
confidence: 99%
“…Room temperature studies are generally standardised at 20–25°C 1 8. Stability data are lacking for many antibiotics in solution above room temperature 9. In warmer climates, the solution temperature may exceed 25°C for over 75% of the 24 hours run-out period, occasionally reaching temperatures of up to 38°C 10.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review published in 2017 found that there were no published studies that complied completely with UK national standards specific to OPAT 9. The UK standards are detailed and describe the minimum data required from a study to be applicable for use in this setting.…”
Section: Introductionmentioning
confidence: 99%